From the cave to the virtual museum: accessibility and democratisation of Franco-Cantabrian Palaeolithic art - Miguel García-Bustos; Olivia Rivero; Paula García Bustos; Ana María Mateo-Pellitero (Virtual Archaeology Review)
Highlights: